Effect of breastfeeding promotions interventions on baby weight at three months of age - S., Krithika; E., Adarsh; V., Rajanish K. (International Journal of Contemporary Pediatrics, 2020)
Background: Breastfeeding is common in developing countries, but exclusive breastfeeding is rare, and complementary foods are introduced to babies at an early age. Despite the proven risks associated with not exclusively breastfeeding, few mothers exclusively breastfeed their babies for six months as recommended by the World Health Organization. The objective of this study was to determine the effect of breast-feeding promotion interventions on baby weight at three months of age. Methods: A randomized experimental study was conducted for a period of 6 months from February 2019 till July 2019 in a tertiary care hospital. Weight- for-age (WA) indices have been determined for 95 infants from three to four months of age, participating in this study. They included 49 that started received promotion interventions support after delivery (till 2 weeks) and 46 that received routine care (control group). Collected data were analysed using SPSS software ver.11.5. Results: Weight-for-age indices were significantly lower for the early group than the control group (p=0.012). They suggest that the breast-feeding promotion interventions are very important educational tools to ensure healthy weight gain in infants. Conclusions: There is evidence that breastfeeding for at least 6 months, compared with feeding formula, prevents the possibility of atopic dermatitis, cow’s milk allergy and early childhood wheezing. Poorer nutritional status was significantly associated with earlier complementary feeding. The results suggest that exclusive breastfeeding along with promotion of weaning education should be promoted in India.